Low-pressure gas breakdown in uniform dc electric field - Lisovskiy, V.; Yakovin, S.; Yegorenkov, V. (JOURNAL OF PHYSICS D: APPLIED PHYSICS, 2000)
This paper studies in experiment and theory the breakdown of argon, nitrogen, air and oxygen in a uniform dc electric field at different discharge gaps L, discharge tube radii R and cathode materials. At arbitrary geometric dimensions of the cylindrical discharge vessel and cathode materials the ratio of the breakdown electric field value to the gas pressure p at the minimum of the breakdown curves is shown to remain constant, (Edc/p)min ≈ constant. A modified breakdown law for the low-pressure dc discharge Udc = f (pL, L/R) is obtained. That is, the breakdown voltage Udc is shown to depend not only on the product pL, but also on the ratio L/R. A method is presented enabling one to predict a dc breakdown curve in the cylindrical discharge vessel possessing arbitrary L and R values from the measured data on the dc breakdown.
Keywords: plasma physics; gas discharges